CONTRACTUAL REGULATION OF LEGAL AID IN LAW FIRMS: NATIONAL AND FOREIGN EXPERIENCE T E Z I S (Conference Zone, 2022)
Thesis is devoted to the study of the features of legal regulation of legal services and conclusion and execution of agreements (contracts) by national and foreign state lawyers. The article analyzes and compares national and foreign experiences. It is concluded that legal aid in advocacy is one of the most complex and theoretically underdeveloped types of assistance, requiring recommendations to address gaps in existing legislation. An analysis of the practical application of legal aid and assignment contracts concluded by lawyers was conducted